The Impact of the Quality of Work Life on Organizational Intelligence - Sardar Ahmad, Brwa; Majed Sadq, Zana; Othman, Bestoon; Hama Saeed, Vian Sulaiman (International Journal of Psychosocial Rehabilitation, 2019)
The quality of work life (QWL) focuses on creating working conditions for an individual working in a healthy and supportive work environment. It can also be seen as a goal that business organizations want to reach. To achieve that goal, organizations need ways to manage its employees, and this is achieved through the philosophy adopted to achieve a quality of work life. The aim of this study is to determine the impact of the quality of work life on organizational intelligence. Primary data collected through a questionnaire and were analyzed by SPSS software. The researchers distributed among 100 employees in governmental banks in Koya City, Kurdistan Region of Iraq. Eighty five (85)forms were returned and seventy six (76) forms were found suitable for the purpose of statistically analyzing. The results found there was an impact of the quality of work life on organizational intelligence and its dimensions.